POLITIK PERDAGANGAN NEGARA-NEGARA AMERIKA UTARA DI TENGAH PESIMISME NAFTA - Demeiati Nur Kusumaningrum; Havidz Ageng Prakoso (Indonesian Association for International Relations, 2022)
Abstract President Trump has insisted on reforming NAFTA on the assumption that this agreement does not benefit America. US citizens have lost jobs, potential environmental damage, and large investments in Meksiko limit the possibility of claiming higher wages for low-income workers in the US. Meanwhile, the wage gap for unskilled workers in Meksiko has also increased in proportion to technological advances resulting from the rapid flow of foreign investment in industry. Increased industrialization has contributed significantly to the conversion of agricultural land and the loss of jobs for traditional farmers in Meksiko. The poverty rate in Meksiko in 2014 was higher than the poverty rate in 1994, causing a trend of Mexican immigration to the United States. Based on trade politics theory, this paper aims to examine the positive and negative implications of implementing the free trade agreement and explain the trade politics of member countries to remain committed to North American trade regionalism. The research found that Meksiko benefited from US and Canadian investment in order to reduce unemployment and support the country's capacity as a production base in the region. Kanada is the main supplier of information and communications technology products to America, while the US maintains its position as the sole player in the automotive sector. Renewal of the agreement to UMSCA is the US response to exclude China from market competition in North America.Keywords: America First; FTA; Regionalism Politics AbstrakPresiden Trump bersikeras mereformasi NAFTA dengan asumsi perjanjian ini tidak menguntungkan Amerika. Warga AS telah kehilangan lapangan kerja, potensi kerusakan lingkungan, dan investasi besar di Meksiko membatasi kemungkinan klaim upah yang lebih tinggi untuk pekerja berpenghasilan rendah di AS. Sementara, kesenjangan upah pada tenaga tidak terampil di Meksiko turut meningkat sebanding dengan kemajuan teknologi yang dihasilkan dari derasnya arus investasi asing di bidang industri. Meningkatnya industrialisasi berkontribusi signifikan terhadap alih fungsi lahan pertanian dan hilangnya pekerjaan petani tradisional di Meksiko. Tingkat kemiskinan Meksiko pada tahun 2014 lebih tinggi dari tingkat kemiskinan tahun 1994 sehingga menyebabkan tren imigrasi Meksiko ke Amerika Serikat. Berdasarkan teori politik perdagangan, tulisan ini bertujuan untuk menelaah implikasi positif dan negatif implementasi kesepakatan perdagangan bebas dan menjelaskan politik perdagangan negara-negara anggota untuk tetap berkomitmen pada regionalisme perdagangan Amerika Utara. Hasil penelitian menemukan bahwa Meksiko diuntungkan dari investasi AS dan Kanada dalam rangka mengurangi pengangguran dan mendukung kapasitas negara sebagai basis produksi di kawasan. Kanada menjadi pemasok utama untuk produk teknologi informasi dan komunikasi ke Amerika, sementara AS mempertahankan posisinya sebagai pemain tunggal dalam sektor otomotif. Perbaharuan perjanjian menjadi UMSCA menjadi respon AS untuk mengeksklusi Cina dari persaingan pasar di Amerika Utara.Kata kunci: America First; Perjanjian Perdagangan Bebas; Politik Regionalisme